Oilseeds: Health Attributes and Food Applications 2020
DOI: 10.1007/978-981-15-4194-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Pumpkin (Cucurbita pepo) Seed

Abstract: A pumpkin seed, also known as a "pepita", means "little seed of squash". Cucurbita pepo is the pumpkin species of the genus: Cucurbita, family: Cucurbits, sub-family: Cucurbitaceae, genera: Cucurbita L. Cucurbita pepo L. is the species among Cucurbitaceae family having the greatest monetary value of the genus. The seeds are typically rather flat, asymmetrically oval, light green in color, and may have a white outer hull. The Cucurbita pepo seeds have potential application and can be used as an alternative oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Also, no negative consequences regarding the laying performance were observed in the experiments. In contrast, there is evidence of a positive influence of pumpkin oil on egg quality and laying performance (Adsul and Madkaikar 2021 ; Herkeľ et al 2014 ). Studies about ripleaf as a main component showed a positive effect on egg production in laying hens (Rahman et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, no negative consequences regarding the laying performance were observed in the experiments. In contrast, there is evidence of a positive influence of pumpkin oil on egg quality and laying performance (Adsul and Madkaikar 2021 ; Herkeľ et al 2014 ). Studies about ripleaf as a main component showed a positive effect on egg production in laying hens (Rahman et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, pumpkin seed oil may be used in a variety of dishes, including pasta, salads, and soups. Moreover, the seeds powder is used in cookies preparation for a healthier recipe (Adsul and Madkaikar, 2021).…”
Section: Role Of Dietary Seeds In Food Industrymentioning
confidence: 99%
“…Pumpkin seed oil is a rich natural source of antioxidant vitamins, tocopherols, and phytosterols and recommended to be used in human diet for health as it mitigates hypercholesterolemia and hypercholesterolemia [ 28 ]. Pumpkin seeds are rich source of essential nutrients posing positive impacts on health [ 29 ]. Oils extracted from raw pumpkin seeds significantly reduced serum triglycerides, total cholesterols, LDL cholesterols, uric acid, creatinine, serum transaminases, and urea, whereas serum HDL cholesterols were significantly increased [ 30 ].…”
Section: Introductionmentioning
confidence: 99%